2015
DOI: 10.1002/2014jc010315
|View full text |Cite
|
Sign up to set email alerts
|

Forced and intrinsic variability in the response to increased wind stress of an idealized Southern Ocean

Abstract: We use ensemble runs of a three layer, quasi-geostrophic idealized Southern Ocean model to explore the roles of forced and intrinsic variability in response to a linear increase of wind stress imposed over a 30 year period. We find no increase of eastward circumpolar volume transport in response to the increased wind stress. A large part of the resulting time series can be explained by a response in which the eddy kinetic energy is linearly proportional to the wind stress with a possible time lag, but no stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…As the ocean integrates the highfrequency atmospheric forcing into lower-frequency variability of the general circulation, links between yearto-year variations in the atmosphere and large-scale ocean circulation are hard to detect. In fact, oceanic EKE variability is largely intrinsic, that is, internally driven, in most regions on interannual time scales (Wilson et al 2015;Rieck et al 2018), which might explain the difficulties previous studies had relating the interannual EKE variability in the WGC to an external forcing (e.g., Luo et al 2011). In the following, we thus focus on variations on decadal time scales.…”
Section: ) Temporal Variabilitymentioning
confidence: 99%
“…As the ocean integrates the highfrequency atmospheric forcing into lower-frequency variability of the general circulation, links between yearto-year variations in the atmosphere and large-scale ocean circulation are hard to detect. In fact, oceanic EKE variability is largely intrinsic, that is, internally driven, in most regions on interannual time scales (Wilson et al 2015;Rieck et al 2018), which might explain the difficulties previous studies had relating the interannual EKE variability in the WGC to an external forcing (e.g., Luo et al 2011). In the following, we thus focus on variations on decadal time scales.…”
Section: ) Temporal Variabilitymentioning
confidence: 99%
“…Studies utilizing ocean general circulation models (OGCMs) have shown this intrinsic variability to manifest itself in sea surface height (SSH) variance (Combes and Di Lorenzo 2007;Penduff et al 2011;Sérazin et al 2015) as well as eddy kinetic energy (Wilson et al 2015). Even properties not directly related to the mesoscale, such as the Atlantic meridional overturning circulation (AMOC) , ocean heat content (Sérazin et al 2017), and sea level trends (Sérazin et al 2016), exhibit intrinsic variability.…”
Section: Introductionmentioning
confidence: 99%
“…The strength of the eddy activity, often measured by the energy carried by the eddies, varies on a variety of time scales ranging from seasonal to decadal (e.g. Stammer and Wunsch, 1999;Qiu, 1999;Penduff et al, 2004;Zhai et al, 2008;Zhai and Wunsch, 2013;Rieck et al, 2015), as a result of both forced and intrinsic variability (Wilson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%